Homozygous CFTR mutation M348K in a boy with respiratory symptoms and failure to thrive: disease-causing mutation or benign alteration? - Hentschel, Julia; Sommerburg, Olaf; Fritzsching, Eva; Mall, Marcus A. (European journal of pediatrics, 2012)
We report on a 6-month-old premature boy from consanguineous parents. He presented with respiratory distress, necrotizing enterocolitis and hyperbilirubinemia shortly after birth. Persisting respiratory symptoms and failure to thrive prompted cystic fibrosis diagnostics, which showed the lack of wild-type signal for the mutation R347P suggesting a homozygous deletion or an alteration different from the known mutation at this position. Sequencing of this region revealed the homozygous substitution 1175 T > A (HGVS: c.1043 T > A) in exon 7 resulting in the homozygous amino acid change M348K. This mutation has never been reported in homozygosity before. Computational analysis tools classified M348K as ‘presumably disease causing.’ In our patient, sweat testing and electrophysiological assessment of CFTR function in native rectal epithelium demonstrated normal Cl− secretion. Conclusion: We assume that the homozygous alteration M348K is a harmless variant rather than a CF-causing mutation.